Visual disgust constricts pupils in response to misophonic movies - Qiu, Yuqi; Park, Sungjoon; Oszczapinska, Urszula; Heller, Laurie M. (Frontiers in Psychology, 2025)
Misophonia is a condition typically described as heightened intolerance to specific everyday sounds, although intense emotional and physiological responses can also be triggered by non-auditory representations of the sources of these sounds, e.g., words, videos, or imagination (Swedo et al., 2022). We asked whether pupillometry could provide an objective pupillary signature of the reactions of disgust and anger toward misophonic events depicted in movies. We found greater pupil constriction toward movies with more visually disgusting video tracks, both for misophonic and non-misophonic individuals, whereas movies with a video track suggesting a neutral source of a misophonic sound (e.g., Samermit et al., 2022, Heller et al., 2025) increased both the sound pleasantness ratings and the pupil diameters. Furthermore, repeated exposure to the same sounds in different movies changed pupil responses such that they diverged from the ratings of sound unpleasantness. The findings of this study may provide valuable insights into the understanding, diagnosis, and treatment of misophonia.